Theoretical and methodological principles for the analysis of the implementation of an in-service teacher education program. - Fabiana Silva Fernandes; Nelson Antonio Simão Gimenes; Vandré Gomes da Silva; Cláudia Oliveira Pimenta (Revista de estudios teóricos y epistemológicos en política educativa, 2019)
The purpose of this article is to present the theoretical and methodological principles of the analysis of the implementation of Tutoria, an in-service teacher education program for school managers and teachers. It focuses not on the results, but rather on strategies and methodological procedures developed in the light of the bottom up approach of studies on public action and the figure of the street bureaucrat. The text is organized to make the theoretical references explicit and then discuss the theoretical-methodological articulations created in the research, which allowed developing categories of analysis and data collection instruments. The research sought to focus on the actions of those who were responsible for implementing the program, the so-called implementing agents, to understand their work routine and the consistency between their actions and the guiding principles of the program. Consequently, the theoretical framework of analysis was studies on the implementation of public policies. As the research was carried out in two different municipalities, an effort of analysis was added: collecting information on the socio-educational context of these municipalities, to understand how the program was executed in different realities. In the implementation study, we sought to understand not only how the program was conceived and structured but also how municipal departments and schools appropriated it. To promote a dialogue that contributes to the advancement of research in the field of analysis of the implementation of public education policies, sharing the methodological paths taken is more important than presenting results.